2017
DOI: 10.1016/j.jacl.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein particle number and size predict vascular structure and function better than traditional lipids in adolescents and young adults

Abstract: Background In adults, dyslipidemia is associated with higher carotid thickness and arterial stiffness, predictors of CV events. In young subjects, lipid concentrations have not been consistently associated with vascular measures. Objective To compare nuclear magnetic resonance (NMR) measures of lipoprotein particle number (LDL-P, HDL-P, VLDL-P) and size (LDL-S, HDL-S, VLDL-S) to determine if they were associated with vascular measures more strongly than lipid concentrations (LDL-C, HDL-C, TG). Methods We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
3
26
0
1
Order By: Relevance
“…In the pediatric First Nation children study, in the presence of elevated TG, only 25% had an elevated LDL-C level compared with 37% with an elevated apo B level [32]. Conventional clinical screening and management of dyslipidemia with a traditional lipid profile may not be as sensitive to detail the overall atherogenic risk [37] and underestimate the severity of dyslipidemia in children and adolescents with T2D, detailed lipoprotein analysis including apo B measurements may be indicated in children and adolescents with T2D.…”
Section: Apolipoprotein B (Apo B) Changesmentioning
confidence: 98%
See 1 more Smart Citation
“…In the pediatric First Nation children study, in the presence of elevated TG, only 25% had an elevated LDL-C level compared with 37% with an elevated apo B level [32]. Conventional clinical screening and management of dyslipidemia with a traditional lipid profile may not be as sensitive to detail the overall atherogenic risk [37] and underestimate the severity of dyslipidemia in children and adolescents with T2D, detailed lipoprotein analysis including apo B measurements may be indicated in children and adolescents with T2D.…”
Section: Apolipoprotein B (Apo B) Changesmentioning
confidence: 98%
“…Lean, obese, and children with T2D are compared.Children with T2D had the largest number of the smallest and most dense LDL-C particles. [37] LDL-C low-density lipoprotein cholesterol, HDL-C high-density lipoprotien cholesterol, VLDL-C very low-density lipoprotein cholesterol, IR insulin resistance, T2D type 2 diabetes mellitus, T1D type 1 diabetes mellitus…”
Section: Treatment Of Elevated Triglyceridesmentioning
confidence: 99%
“…The small LDL particles are considered more atherogenic than the large LDL particles with previous studies showing that lower levels of LDL and HDL mean particle sizes are associated with insulin resistance [14, 15]. Two recent large scale studies in obese, pre-diabetic, and type 2 diabetic adolescents and young adults showed that NMR lipid profile is a better indicator of vascular damage compared to the traditional lipid profile [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, vascular TOD can be found in high-risk youth related to elevated cardiovascular risk factors. Higher cIMT is found in youth with obesity, 45 dyslipidemia, and clustering of cardiovascular risk factors. 46 Day et al performed a systematic review of over 300 articles to evaluate whether there was an independent relationship between blood pressure and cIMT in youth, and examined 28 of those studies that measured clinic blood pressure in detail.…”
Section: Vascular Target Organ Damage Related To Blood Pressure Inmentioning
confidence: 96%